Gender differences in the modifying effect of living arrangements on the association of sleep quality with cognitive function among community-dwelling older adults: a cross-sectional study - Yang, Haifeng; Xu, Lingzhong; Qin, Wenzhe; Hu, Fangfang; Li, Lei; Chen, Chenhui; Tang, Wenlong (Frontiers in Public Health, 2023)
Background: Sleep quality is considered to be associated with cognitive function for older adults, but little is known whether living with others can buffer mild cognitive impairment in older adults with poor sleep quality. The objective of this study was to examine the role of living arrangements in sleep quality and cognitive function among older adults aged 65 and over. Methods: 2859 older adults over 65 years old were selected by using multi-stage stratified sampling method. Cognitive function and sleep quality were measured using Mini-Mental State Examination (MMSE) and Pittsburgh Sleep Quality Index (PSQI). Binary logistic regression was performed to examine the relationship between sleep quality and mild cognitive impairment, and the interaction effects of sleep quality and living arrangements on mild cognitive impairment stratified by gender. Results: Poor sleep quality was associated with mild cognitive impairment among men and women regardless of living arrangements. The significantly protective role of living with others on reducing the incidence of mild cognitive impairment was found in men with poor sleep quality, but not in women. Conclusion: Targeted support for older adults with poor sleep quality may be effective in preventing mild cognitive impairment, and gender differences should be taken into account when promoting cohabitations.